2019
DOI: 10.3390/jcm9010082
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding in Patients with Hereditary Hemorrhagic Telangiectasia: Risk Factors and Endoscopic Findings

Abstract: Background: We aimed to describe risk factors for gastrointestinal (GI) bleeding and endoscopic findings in patients with hereditary hemorrhagic telangiectasia (HHT). Methods: This is a prospective study from a referral HHT unit. Endoscopic tests were performed when there was suspicion of GI bleeding, and patients were divided as follows: with, without, and with unsuspected GI involvement. Results: 67 (27.9%) patients with, 28 (11.7%) patients without, and 145 (60.4%) with unsuspected GI involvement were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Canzonieri et al and van Tuyl et al systemically studied the extent of GI involvement with gastroscopy, video capsule endoscopy, and colonoscopy in 22 and 35 HHT patients, respectively, and found a higher prevalence of telangiectasia in patients with ENG mutation [8,35,36]. In a recent study, Mora-Luján et al reported that age, tobacco use, ENG mutation, and hemoglobin levels were associated with GI involvement in HHT comparing 67 patients with GI disease and 28 with negative GI study [37]. However, Berg et al, Sabbà et al and Letteboer et al assessing genotype-phenotype relationship in HHT patients, reported a similar incidence of GI telangiectasia in HHT1 and HHT2 patients [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Canzonieri et al and van Tuyl et al systemically studied the extent of GI involvement with gastroscopy, video capsule endoscopy, and colonoscopy in 22 and 35 HHT patients, respectively, and found a higher prevalence of telangiectasia in patients with ENG mutation [8,35,36]. In a recent study, Mora-Luján et al reported that age, tobacco use, ENG mutation, and hemoglobin levels were associated with GI involvement in HHT comparing 67 patients with GI disease and 28 with negative GI study [37]. However, Berg et al, Sabbà et al and Letteboer et al assessing genotype-phenotype relationship in HHT patients, reported a similar incidence of GI telangiectasia in HHT1 and HHT2 patients [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Plauchu et al reported that only 1.5% of patients had GI bleeding at ages younger than 30 [28]. In adults, anemia is a typical complication of chronic GI bleeding in HHT [6,[36][37][38], and Kasthuri et al described GI bleeding as an independent predictor of anemia in adult HHT patients [12]. Given the typically later-life onset of GI bleeding, the current HHT guidelines [6] recommend monitoring hemoglobin and hematocrit after the age of 35, as a marker of GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The association between genotype, epistaxis, and visceral AVMs has been previously evaluated [6,13,14,[29][30][31][32]. Epistaxis is the most common (> 90%) manifestation in patients with both ENG and ACVRL1 mutations, although patients with ENG mutations are believed to have onset of epistaxis at a younger age [6,[13][14][15]33].…”
Section: Discussionmentioning
confidence: 99%